Face-on orientation of fluorinated polymers conveyed by long alkyl chains: a prerequisite for high photovoltaic performances. Issue 25 (12th June 2018) - Ibraikulov, Olzhas A.; Ngov, Chheng; Chávez, Patricia; Bulut, Ibrahim; Heinrich, Benoît; Boyron, Olivier; Gerasimov, Kirill L.; Ivanov, Dimitri A.; Swaraj, Sufal; Méry, Stéphane; Leclerc, Nicolas; Lévêque, Patrick; et al.
Abstract : F substituents & bulky alkyl side-chains for polymer:fullerene face-on orientation and high PV performances. Abstract : The recently reported high power conversion efficiencies achieved in fluorinated polymer:fullerene solar cells have been accounted for by the presence of face-on oriented polymer backbones that enable charge transport towards the collecting electrodes. In this work, we demonstrate that, in contrast to the results of a number of reports, the face-on polymer orientation is due to the bulky side chains, rather than to aggregation in solution. This conclusion is supported by a comparative study of polymers having similar conjugated backbones but different number of fluorine atoms and different number and type of alkyl side chains. While the latter are primarily introduced to tune polymer solubility, the present in-depth thin-film morphology investigation shows that increasing the chain bulkiness favors formation of crystalline lamellae with face-on oriented backbones, independently of the degree of fluorination. By contrast, introduction of fluorine atoms is found to substantially enhance the π-stacking interactions that remain invariably strong upon blending of the polymer with fullerene. Our results demonstrate that, for the polymer family under investigation, fluorination and functionalization by bulky alkyl side chains are both needed for reaching power conversion efficiencies above 10%.